O som no cinema brasileiro : revisão de uma importância indeferida - Costa, Fernando Morais da (2007)
This work aims to reaffirm the central role played by sound in Brazilian cinema. It describes periods when changes related to sound recording and editing transformed the ways of making and watching films in Brazil. It details the first methods of syncronizing sound and images between 1902 and 1908. It coments the end of the silent era and the making of the first Brazilian sound films in the late 1920’s up to 1936, the period when the first sucessfull musical comedies would be released. During the 60’s the arrival of portable sound recorders would allow new ways of shooting, as well as new forms of assembling sounds and images. It discusses the role given to sound in contemporary Brazilian films. What novelties reside within their soundtracks?